2019
DOI: 10.1080/00405000.2019.1694353
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose-based fibres derived from palm oil by-products and theirin vitrobiocompatibility analysis

Abstract: Fibres with nanocellulose isolated from oil palm empty fruit bunches (OPEFBs) were produced. Nanocellulose and PVA-nanocellulose fibres were prepared by wet spinning in an acetone coagulation bath without drawing. The addition of nanocellulose was varied from 10% to 30%, to reveal the beneficial effects of nanocellulose content on the properties of produced spun-fibres. Higher concentration of nanocellulose increased the stiffness of spun-fibres. PVA and PVA-bacterial cellulose fibres were also produced as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Nanocellulose processed from oil palm empty fruit bunches (OPEFBs) was used to fabricate filaments, which were compared to neat poly(vinyl alcohol) (PVA)‐filaments and PVA‐bacterial nanocellulose filaments as control. [ 46 ] The filaments were wet‐spun and subsequently coagulated in acetone. For these hybrid filaments, nanocelluloses were added in the range 10–30 wt%, and mechanical tests were performed in dry and wet states.…”
Section: Improvements and Tuning Of Filament Propertiesmentioning
confidence: 99%
“…Nanocellulose processed from oil palm empty fruit bunches (OPEFBs) was used to fabricate filaments, which were compared to neat poly(vinyl alcohol) (PVA)‐filaments and PVA‐bacterial nanocellulose filaments as control. [ 46 ] The filaments were wet‐spun and subsequently coagulated in acetone. For these hybrid filaments, nanocelluloses were added in the range 10–30 wt%, and mechanical tests were performed in dry and wet states.…”
Section: Improvements and Tuning Of Filament Propertiesmentioning
confidence: 99%
“…Moreover, Poonguzhali et al [27] reported that nanocellulose incorporation up to 10% into chitosan/poly(vinyl pyrrolidone) matrix improved wound healing yarn with a tensile strength of 39.7 ± 6.9 MPa. Similar nanocellulose reinforcements in various blend polymers have also been demonstrated [13,15,28]. In addition, Li et al [29] also found that adding a small amount of long filamentous nanocellulose fibrils (NCFs) into PVA films increased the maximum degradation temperature around 4 to 16.9 °C indicating that nanocellulose addition also could enhance the thermal stability of the PVA films.…”
Section: ■ Introductionmentioning
confidence: 64%
“…Nowadays, many researchers have focused on the use and recycling of OPEFBs because of their exceptional potential as an organic carbon source and sustainability in producing high value-added materials, such as activated carbon [5][6][7][8], bioethanol [9][10][11][12], and nanocellulose [13][14][15][16]. Among them, nanocellulose has been an up-andcoming class of materials, which has a broad spectrum of applications, including food packaging [17], tissue engineering [18], pharmaceutics [19], and wound treatment [20][21].…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of development and cost of achieving the end result is still in the custody of advanced countries such as the USA, Germany, Japan, and France, as nice and promising as nanotechnology seems to be. In the agricultural production of the country, a significant share of work falls on both circular and frontal multisupport sprinkling machines [6]. They have highquality indicators, low labor intensity when using, and a large irrigation area.…”
Section: Introductionmentioning
confidence: 99%